EFFECT OF VARIATION OF CEMENT WATER FACTOR IN CONCRETE MIXTURE WITH THE ADDITION OF PALM SHELL ON THE PRESSIVE STRENGTH OF NORMAL CONCRETE - Teuku Farizal; Samsunan; Aulia Rahman; Murhaban; Al Munawir; Herri Darsan (RADJA PUBLIKA, 2023)
Palm shell is a waste from palm oil production which is shaped like a shell with a hard layer character that aims to protect the palm kernels. The addition of palm shells to concrete is an innovation and breakthrough in the more productive use of palm oil waste. In this study, the percentage of addition of palm shells was used, among others, 0%, 7% and 14% by weight of cement with variations in the cement water factor (FAS) of 0.35, 0.45 and 0.50. The test object used was a cube (15 x 15 x 15) cm with a total of 9 test objects for each FAS with a test time of 28 days. The results of the concrete compressive strength test obtained data for FAS 0.35, the average compressive strength for BTCS was 348.15 kg/cm2, BDCSA (7%) was 363.07 kg/cm2 and BDCSB (14%) was 302.90 kg/cm2. FAS 0. 45 the average compressive strength for BTCS was 292.59 kg/cm2, BDCSA (7%) was 303.20 kg/cm2 and BDCSB (14%) was 249.27 kg/cm2. FAS 0.50 average compressive strength for BTCS was 273.09 kg/cm2, BDCSA (7%) was 271.53 kg/cm2 and BDCSB (14%) was 219.47 kg/cm2. The test results show that the average concrete compressive strength is influenced by the cement water factor (FAS) and the percentage of addition of palm shells in the concrete mix.